Nazi war criminals - Rice, Earle, Jr., 1928- (San Diego, CA : Lucent Books, 1998)
Explores the lives of six Nazi war criminals and the roles they played in implementing the Final Solution to the Jewish Question.
Includes bibliographical references (p. 98-104) and index.
Keywords: Nuremberg Trial of Major German War Criminals, Nuremberg, Germany, 1945-1946 -- Juvenile literature; War crime trials -- Germany -- Nuremberg -- Juvenile literature; Nuremberg Trial of Major German War Criminals, Nuremberg, Germany, 1945-1946.; War crime trials